Women and the payscales overcoming the imbalance - Bello, Margaret F. (Society Publishing, 2019)
Gender pay parity has been a comprehensively debated topic across the world. However, males and females at equal or equivalent jobs can be seen paid differently due to gender bias. Paying the men should not be more for performing a particular task just because they are men. Repeatedly, women have raised parity issues in public but it seems that their voices only have to face ignorance. There have been multiple issues of biases against women but paychecks are one of the grey areas, which are most often not chosen to be addressed. In order to attain pay parity for women, a study called "Women and the pay scales: overcoming the imbalance" has been developed.